Pengaruh Mutu Pelayanan Farmasi terhadap Kepuasan dan Loyalitas Pasien Rawat Jalan dengan Cara Bayar Tunai - Sa'adah, Evi; Hariyanto, Tatong; Rohman, Fatchur (Universitas Brawijaya, Indonesia, 2015)
This study aimed to determine the patient's effect of the pharmaceutical service quality on satisfaction and loyalty in an outpatient pharmacy depot of Gambiran Regional Public Hospital Kediri. This study is a quantitative observational study using cross-sectional approach with 115 respondents. Sampling technique used in this study is purposive sampling method. Hypothesis testing is performed using Structural Equation Modeling (SEM). The hypothesis is evaluated based on the Critical Ratio (CR)>1.96 and the probability (p)<0.05. The results showed that pharmaceutical services is positively and significantly effect the patient satisfaction with the size of the coefficient of 0.881. The results also showed that the pharmaceutical service has no effect on patient loyalty and showed that satisfaction is positively and significantly effect the patient loyalty with the coefficients as large as 0.814. The study also showed that the pharmaceutical service influence patient loyalty indirectly through satisfaction.